2011
DOI: 10.1021/ja202874d
|View full text |Cite
|
Sign up to set email alerts
|

Enantiocontrolled Total Syntheses of Breviones A, B, and C

Abstract: Enantiocontrolled total syntheses of the breviones A, B, and C have been accomplished using a highly diastereoselective oxidative coupling of an α-pyrone with a tricyclic diene prepared from an optically pure Wieland-Miescher ketone derivative through the 7-endo-trig mode of acyl radical cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 50 publications
0
28
0
1
Order By: Relevance
“…Although the formation of 7 is likely to depend on the addition speed of MeMgBr (slow addition of MeMgBr led to significant formation of 25 ), we investigated other transition metal‐catalyzed methods for methylation of 22 to obtain the desired 7 more consistently. Although Stille coupling using tetramethyltin or Suzuki−Miyaura coupling using trimethylboroxine gave 7 in moderate yield, the concomitant formation of dimers 26 (entry 2) or 27 and 28 (entry 3) was observed. Although Negishi coupling with dimethylzinc also generated dimer 26 , the desired 7 was obtained in 75 % yield, comparable with the best result (entry 1), but in a more reproducible manner (entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…Although the formation of 7 is likely to depend on the addition speed of MeMgBr (slow addition of MeMgBr led to significant formation of 25 ), we investigated other transition metal‐catalyzed methods for methylation of 22 to obtain the desired 7 more consistently. Although Stille coupling using tetramethyltin or Suzuki−Miyaura coupling using trimethylboroxine gave 7 in moderate yield, the concomitant formation of dimers 26 (entry 2) or 27 and 28 (entry 3) was observed. Although Negishi coupling with dimethylzinc also generated dimer 26 , the desired 7 was obtained in 75 % yield, comparable with the best result (entry 1), but in a more reproducible manner (entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…A number of total syntheses 16-19 of natural products have been reported by reducing (-)- 8 to alcohol (-)- 10 followed by the treatment with sodium methoxide in methanol and EVK to give (+)- 11 . However, the ee of (+)-11 has decreased significantly to 23.5% ee.…”
Section: Resultsmentioning
confidence: 99%
“…To our delight, lithium-liquid ammonia reduction of the enone function of (-)- 12 followed by ethyl α-(trimethylsilyl)vinyl ketone and cyclization with KOH in methanol afforded (+)- 13 as a single stereoisomer [presumably in optically pure form since C4a and C5 of (-)- 12 should not be affected under the reaction conditions]. Reductive methylation of the enone function of (+)- 13 with lithium in liquid ammonia/methyl iodide followed by protection of the resulting ketone function with ethylene glycol under acidic medium gave (-)- 14 , which was readily converted into (-)- 7 19 by removal of the TBS protecting group and subsequent IBX-DMSO oxidation (Scheme 1). Compound (-)- 7 possesses specific rotation [α] D 25 = -28 (c = 0.14, CHCl 3 ), which is slightly larger than that reported ([α] D 25 = -26; 98% ee) 19 using the same solvent and concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 2 and 3 are closely related to the known breviones A ( 5 ) and B ( 6 ) [10,11], respectively, but differ in having a hydroxy group at C-11, whereas compound 4 has a ketone group at C-11 compared to the co-isolated known compounds 7 and 8 [8]. To date, total syntheses of several breviane spiroditerpenoids have been achieved [23,24,25,26,27] including the enantioselective synthesis of breviones A–C [27]. In the current work, the isolation of additional new secondary metabolites, especially the structurally unique sterol demonstrated that the marine-derived fungi from deep water sediments deserve increased attention.…”
Section: Discussionmentioning
confidence: 99%